KONSEP PENGEMBANGAN KOTA BANDA ACEH SEBAGAI KOTA WISATA TSUNAMI - Elysa Wulandari; Desi Safriana (Jurnal Arsitektur ARCADE, 2017)
ABSTRACT: The city of Banda Aceh has experienced several tsunamis that destroy civilization on it. Currently every year tsunami warnings are conducted both national and international scale, both academic and tourism purposes. The warning brings many people who need information about the existence of the city of Banda Aceh from previous times. Therefore it is necessary to extract and study the important objects that describe the past civilization of the city of Banda Aceh, to be realized as part of the space elements of today's city of Banda Aceh. The study was conducted on several important objects from the XVII century on the coast that gave the image of the city of Banda Aceh as a cosmopolitan city and a maritime city. Approach the study by revealing the architectural aspect of the object and the proposed zoning pattern in each object. The results of the discussion appear to present historical stories through replicas of objects and graves that have a place to contemplate as a support facility. The conclusion of the paper provides a theoretical framework on tsunami impact tourism development in the city of Banda Aceh. This paper is considered important as one way of strengthening the self of the Indonesian nation about the disclosure of glory and identity of the past, useful for building the character of the nation. Besides, it is also to open the insight for the government and city development actors in preparing the city of Banda Aceh as a tourist city of the tsunami. Keywords: Banda Aceh City, Tsunami Tourism, Architectural Design  ABSTRAK: Kota Banda Aceh telah mengalami beberapa kali tsunami yang merusak peradaban di atasnya. Saat ini setiap tahun dilaksanakan peringatan tsunami baik skala nasional maupun international, baik tujuan akademik maupun pariwisata. Peringatan tersebut menghadirkan banyak orang yang membutuhkan informasi tentang keberadaan kota Banda Aceh dari masa-masa sebelumnya. Oleh karena itu diperlukan penggalian dan kajian objek penting yang menggambarkan peradaban masa lalu kota Banda Aceh, untuk diwujudkan sebagai bagian elemen ruang kota Banda Aceh masa kini. Kajian dilakukan pada beberapa objek penting mulai dari abad XVII di bagian pesisir yang memberi citra kota Banda Aceh sebagai kota kosmopolitan dan Kota maritim. Pendekatan kajian dengan mengungkapkan aspek arsitektural objek dan usulan pola penataan zona di setiap objek. Hasil pembahasan tampak bahwa menghadirkan cerita sejarah melalui replika objek dan kuburan yang dilengkapi tempat untuk berkontempelasi sebagai fasilitas pendukung. Kesimpulan tulisan memberikan kerangka teoritik tentang pengembangan objek wisata dampak tsunami di kota Banda Aceh. Tulisan ini dirasa penting sebagai salah satu cara penguat jadi diri bangsa Indonesia tentang pengungkapan kejayaan dan identitas masa lalu, berguna bagi membangun karakter bangsa. Disamping itu juga untuk membuka wawasan bagi pemerintah dan pelaku pembangunan kota dalam menyiapkan kota Banda Aceh sebagai kota wisata tsunami.